THE USE OF PICTURE BOOK IN TEACHING READING FOR JUNIOR HIGH SCHOOL STUDENTS - Maulana Restanto (Journal of English and Education, 2016)
The research was aimed at discovering the use of picture book in helping junior high school students learn reading narrative, and the students’ responses to the use of picture book in teaching reading for junior high school students. The picture book in this research was Dr. Seuss's